Multimodal Freight Transport and Urban Rural Connectivity in Emerging Economic Regions of Indonesia: JEL Classification: R41, R42, L91, R11, O18 - Nurullah Budisiswanto (Journal of Management and Administration Provision, 2026)
This study examines how multimodal freight transport can improve urban and rural connectivity and promote balanced regional development in the Ciayumajakuning region of West Java, Indonesia, comprising Cirebon, Indramayu, Majalengka, and Kuningan. Although the region has strong industrial and agricultural potential, fragmented logistics systems and poor transport integration continue to constrain economic growth. A qualitative descriptive approach was employed, combining spatial and temporal analysis using secondary data from regional planning documents, national logistics statistics, GIS mapping, and stakeholder interviews. The study evaluated transport development from 2010 to 2025, compared district performance, and identified infrastructure gaps affecting regional economic integration. The findings indicate that road infrastructure has received the largest investment, improving connectivity in urban areas such as Cirebon. However, rural districts, particularly Indramayu and Kuningan, continue to experience inadequate transport infrastructure and weak integration between road, rail, and maritime networks. Limited port capacity, insufficient rail connections, and heavy dependence on road transport increase logistics costs and reduce efficiency. The results demonstrate that stronger multimodal connectivity enhances market access, reduces transportation costs, and accelerates freight movement between urban and rural areas. The study recommends developing integrated logistics hubs, expanding rail and port infrastructure, strengthening public private partnerships, and improving coordination between national and regional transport policies. These strategies can support more inclusive regional development and provide a practical model for sustainable logistics integration in emerging economic regions of Indonesia.